Análisis de la imagen interna de la institución universitaria: Contruccción de un modelo para la obtención de la imagen bajo la perspectiva del alumno - J. Traverso Cortés; M. L. Román Onsalo (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2007)
Nowadays, the managements of the spanish universities face a series of challenges that they force them to reconsider their administration models with the purpose of obtaining a solid competitive position. For it the present work analyzes the obtaining of sustainable competitive advantages through the administration of an intangible resource as it is the institutional image. This work a model formulates and develops for the determination of the internal image of the university institution, under the perspective of the collective students. The practical application of the pattern is developed in the University of Seville. Equally this is proven the evolution from the pattern when changing diverse characteristics of the studied group.
Keywords: 330; image; university institution; theoretical model